Wiley Encyclopedia of Electrical and Electronics Engineering 1999
DOI: 10.1002/047134608x.w4333
|View full text |Cite
|
Sign up to set email alerts
|

Theorem Proving

Abstract: The sections in this article are History, Status, and Future Prospects Propositional Logic Propositional Proof Procedures First‐order Logic First‐Order Proof Systems Equality Other Logics Current Research Areas Acknowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Robinson and Voronkov, 2001 is a handbook covering just deductive methods, techniques, and systems. Plaisted, 2009 is an encyclopedia article similar to the present one. Ongoing research is reported in the Journal of Automated Reasoning (Kluwer Academic Publishers) and in the proceedings volumes (published by Springer Verlag) of the International Conferences on Automated Deduction as well as in other journals and conferences.…”
Section: Psychology Of Reasoningmentioning
confidence: 85%
“…Robinson and Voronkov, 2001 is a handbook covering just deductive methods, techniques, and systems. Plaisted, 2009 is an encyclopedia article similar to the present one. Ongoing research is reported in the Journal of Automated Reasoning (Kluwer Academic Publishers) and in the proceedings volumes (published by Springer Verlag) of the International Conferences on Automated Deduction as well as in other journals and conferences.…”
Section: Psychology Of Reasoningmentioning
confidence: 85%